Plan graphics - Davis, David A.; Walker, Theodore D. 4 0 16; Walker, Theodore D.;Walker, Theodore D.; 5 (New York : John Wiley, 2000)
Provides full-color examples of architectural design presentation graphics, covering all phases of the design process.
Walker's name appears first on the earlier edition.;Published simultaneously in Canada--T.p. verso.;Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Architectural drawing.;Architectural drawing; 20; 2